Inside-Out Antegrade Tibial Tunnel Drilling Through the Posterolateral Portal Using a Flexible Reamer in Posterior Cruciate Ligament Reconstruction - Alentorn-Geli, Eduard (Arthrosc Tech, 2015)
Posterior cruciate ligament (PCL) reconstruction using the transtibial drilling or arthroscopic tibial-inlay technique has a risk of injury to the popliteal neurovascular bundle because a pin is drilled anterior to posterior. Intraoperative fluoroscopy is used to decrease the risk of neurovascular injury. In addition, graft passage in the transtibial technique may be problematic because of a sharp turn when placing the graft into the tibial tunnel, which may damage graft fibers. In the surgical technique described in this report, the posteromedial portal is used for visualization and the posterolateral portal is used for debridement of the PCL tibial footprint and the synovial fold closest to the PCL. A curved guide is placed from the posterolateral portal to the tibial footprint, and a flexible pin is drilled across the tibia. The tibial tunnel is then created using a flexible reamer under direct visualization up to the desired length, and a graft can be positioned in the tibial tunnel through the posterolateral portal. This technique has the potential advantages of decreasing the risk of injury to the popliteal neurovascular bundle (use of anteriorly directed, inside-out drilling), avoiding a sharp turn during graft passage, and allowing accurate and anatomic tibial tunnel placement without intraoperative fluoroscopy.